Pattern analysis, intelligent security and the Internet of things - Abraham, Ajith 1968-; Muda, Azah Kamilah; Choo, Yun-Huoy (Springer International Publishing, 2015)
This Volume presents the selected papers from the 5 Parallel Symposiums of the 2014 Fourth World Congress on Information and Communication Technologies (WICT 2014) held in Malacca, Malaysia. The theme of WICT 2014 'Innovating ICT for Social Revolutions'. WICT 2014 is Co-Organized by Machine Intelligence Research Labs (MIR Labs), USA and Universiti Teknikal Malaysia Melaka, Malaysia. WICT 2014 is technically co-sponsored by IEEE Systems, Man & Cybernetics Society Malaysia and Spain Chapters and Technically Supported by IEEE Systems Man and Cybernetics Society, Technical Committee on Soft Computing.